Improving Employee Performance Quality Through Training and Work Life Balance: Literature Review - Rizqulloh, Ahmad Dafa Bahits; Kuncoro, Wicaksono Andy; Hidayati, Retno; Lataruva, Eisha (Research Horizon, 2024)
Employee empowerment is a major focus in organizations because it plays an important role in improving performance. By improving employee skills and motivation, organizations can create a positive impact on work productivity and effectiveness. However, companies are faced with challenges in implementing empowerment practices, such as changing organizational culture and overcoming resistance to change. Therefore, companies must proactively address these challenges to optimize employee empowerment and achieve organizational goals. The concept of employee empowerment involves key elements such as providing autonomy in decision-making, providing training and skills development, and creating strong managerial support. In addition, open communication and policies that support work-life balance also contribute to employee empowerment. By implementing strategies such as rewarding achievements, working time flexibility, and career development opportunities, companies can create a supportive atmosphere. This study uses the literature review method to evaluate the impact of empowerment through training and work-life balance on employee performance. The results show that training and work-life balance consistently have a positive impact on employee performance.